TRANSAKSI E-COMMERSE DALAM EKONOMI SYARIAH - Mahmuda Mulia Muhammad (El-Iqthisadi, 2020)
AbstractThe advancement of telecommunications, information and computer technology has led to changes in culture and the demands of everyday life, so that it has given birth to new patterns of relationships, including in the business world. One of its flagship media is through e-commerce (electronic commerce). The emergence of concerns about e-commerce transactions, especially the Islamic community in Indonesia, both from a security perspective and a sharia perspective. This paper aims to analyze e-commerce transactions in Islamic economics. The results of the analysis concluded that technically the transaction, both in the form of buying and selling services or goods, if the goods are delivered in a formidable form of non-digital, then e-commerce transactions can be analogous to the sale of al-salam, which has been prescribed from the beginning- the beginning of Islam through the Sunnah of the Holy Prophet. The use of e-commerce in Indonesia is permitted while the two parties understand each other. This article is also to provide general guidance about e-commerce users in running their business. Keywords: Bai 'as-salam, E-Commerce, Islamic Economics.AbstrakKemajuan teknologi telekomunikasi, informasi dan komputer, telah menyebabkan terjadinya perubahan kultur dan tuntutan hidup sehari-hari, sehingga telah melahirkan pola hubungan baru, di antaranya dalam dunia bisnis. Salah satu media andalannya adalah melalui e-commerce (electronic commerce). Munculnya kekhawatiran terhadap transaksi e-commerce khususnya masyarakat Islam di Indonesia, baik dari prespektif keamanan dan prespektif syariah. Tulisan ini bertujuan untuk menganalisis transaksi e-commerce dalam ekonomi syariah. Hasil analisis disimpulkan bahwa secara teknis transaksinya, baik dalam bentuk jual-beli jasa atau barang, kalau barang tersebut diserahkan secara tangguh karena berbentuk non digital, maka transaksi e-commerce dapat dianalogikan kepada jual-beli al-salam, yang telah disyariatkan semenjak awal mulanya Islam melalui Sunnah Nabi saw. Penggunaan e-commerce di Indonesia dibolehkan selagi antara kedua belah pihak saling paham. Artikel ini juga untuk memberikan panduan umum tentang pengguna e-commerce dalam menjalankan bisnisnya.Kata Kunci : Bai’ as-salam, E-Commerce, Ekonomi Syariah.